Assistance for Sugarcane Cultivation and Post-Harvest Processing as a Regional Superior Product in Nagari Talang Babungo, Solok Regency - Resti - Fevria; Vauzia Vauzia; Yulkifli Yulkifli; santi Diana Putri; Roni Jarlis (Fakultas MIPA Universitas Negeri Padang, 2025)
Nagari Talang Babungo in Solok Regency, West Sumatra, exhibits significant potential for sugarcane (Saccharum officinarum L.) cultivation. While the current average sugarcane yield in this area is 70 tons/ha, the maximum potential could reach 150 tons/ha. This research aims to enhance sugarcane productivity through the application of biochar, produced from agricultural waste including bagasse, as a soil amendment. Biochar has been shown to improve soil fertility and nitrogen use efficiency in plants. To capitalize on this potential, a comprehensive mentoring program has been implemented to enhance farmers' knowledge and skills in sugarcane cultivation and post-harvest processing techniques. Results demonstrate that biochar application can increase sugarcane biomass production by up to 23% and improve nitrogen use efficiency by up to 35%. Moreover, the socialization and training initiatives have significantly improved farmers' understanding, with average participant scores rising from 42.3 to 85.7 after program completion. The integration of biochar application and effective training not only boosts sugarcane productivity but also supports local economic development and agricultural sustainability in Nagari Talang Babungo. This program aligns with local government policies aimed at enhancing food security and agricultural productivity, thus contributing to the region's overall development strategy.